Chemoautotrophic growth of ammonia-oxidizing Thaumarchaeota enriched from a pelagic redox gradient in the Baltic Sea - Berg, Carlo; Listmann, Luisa; Vandieken, Verona; Vogts, Angela; Jürgens, Klaus (Frontiers in Microbiology, 2015)
Ammonia-oxidizing archaea (AOA) are an important component of the planktonic community in aquatic habitats, linking nitrogen and carbon cycles through nitrification and carbon fixation. Therefore, measurements of these processes in culture-based experiments can provide insights into their contributions to energy conservation and biomass production by specific AOA. In this study, by enriching AOA from a brackish, oxygen-depleted water-column in the Landsort Deep, central Baltic Sea, we were able to investigate ammonium oxidation, chemoautotrophy, and growth in seawater batch experiments. The highly enriched culture consisted of up to 97% archaea, with maximal archaeal numbers of 2.9 × 107 cells mL-1. Phylogenetic analysis of the 16S rRNA and ammonia monooxygenase subunit A (amoA) gene sequences revealed an affiliation with assemblages from low-salinity and freshwater habitats, with Candidatus Nitrosoarchaeum limnia as the closest relative. Growth correlated significantly with nitrite production, ammonium consumption, and CO2 fixation, which occurred at a ratio of 10 atoms N oxidized per 1 atom C fixed. According to the carbon balance, AOA biomass production can be entirely explained by chemoautotrophy. The cellular carbon content was estimated to be 9 fg C per cell. Single-cell-based 13C and 15N labeling experiments and analysis by nano-scale secondary ion mass spectrometry provided further evidence that cellular carbon was derived from bicarbonate and that ammonium was taken up by the cells. Our study therefore revealed that growth by an AOA belonging to the genus Nitrosoarchaeum can be sustained largely by chemoautotrophy.